The Portrayal of Abbasid Rulers in Chronography of Theophanes the Confessor - Cecota, Błażej (Studia Ceranea, 2022)
This text supplements another, a paper presented a decade ago on the portrayal of Umayyad rulers in Chronography of Theophanes the Confessor (B. Cecota, Islam, the Arabs and Umayyad Rulers according to Theophanes the Confessor’s Chronography, “Studia Ceranea” 2, 2012, p. 97–111). I am limiting myself here to discussing only those source remarks which directly concern one of the Abbasid Caliphs, or alternatively, to narratives structured in such a manner that they implied certain traits of a ruler. General remarks concerning the portrayal of the entire dynasty have been included, both in the main text and in the footnotes, only where this was necessary for the understanding of the context in which the Caliphs’ descriptions appear.